Evaluation of Wagon Impact Tests by Various Measuring Equipment and Influence of Impacts on Cargo Stability - Jan Zamecnik; Juraj Jagelcak (Communications, 2015)
This article deals with impact tests of wagons, evaluation of impacts from various measuring equipment and influence of impacts on cargo motion in the wagons when various manners of cargo securing were used. The accelerations generated during impacts were observed also by monitoring units designed for monitoring of transport and by recordings from cameras GoPro Hero. Instead of observing the influence of impacts on the cargo loaded in impacting wagons, the function of the monitoring units in a closed building with not very good GPS signal was also observed.